Blood Cancer: A curse - Samal, Priyanka; Patra, Pritish Chandra (International Journal of Psychosocial Rehabilitation, 2019)
A large variety of different malignancies are caused by blood cancer. This group includes lymph node, lymph tube, tonsil, thymus, spleen and digestive lymph tissue cancer, blood and lymphatic system. The most common types of blood cancer are leukemia, myeloma, starting at the bone marrow, and lymphoma, beginning in the lymphatic system. It is not clear what causes these cancers. With the development of leukemia and myeloma inside the bone marrow, it can hinder the capacity of the bone marrow to produce normal blood cells, including white blood cells, red blood cells and platelets. This can lead to recurrent infections, anemia and quick flushing. Lymphomas, which usually appear as lymph node enlargement, can also prevent the body from fighting infections. Therefore, myelomas create an abnormal protein which causes symptoms in other parts of the body, weakens the bones. The diagnosis of blood cancer has improved significantly, leading to higher remission and survival rates. Remission takes place when no cancer symptom is present. Nearly 1 million people today in the United States experience or have recovered from cancer of the blood. Blood cancer patients may have bleeding problems. Today, cancer is a household word, with at least one close person, a relative or friend, a neighbor or colleague, being diagnosed with cancer, being closely associated with human beings.